Para uma definição de tempo livre tendo as crianças por medida e referente. O que diz a língua dos pássaros? - Araújo, Maria José; Monteiro, Hugo (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
In this text, we conceive free time and the “freedom” of free time as specific affirmations of the right to an infancy with rights. Listening-in to an example by Giorgio Agamben, who personified a Benjaminian idea of “free prose” in the fable of the “Sonntagskinder”, the children who “can understand the language of birds” (2013: 27), we put forward critical hypotheses that enable a broader experience of education from children's concrete and effective words in choosing the definition and enjoyment of time, space in their own meanings.